Covid-19 Outbreak In Italy: Are We Ready for the Psychosocial and the Economic Crisis? Baseline Findings From the PsyCovid Study - Cerami, Chiara; Santi, Gaia C.; Galandra, Caterina; Dodich, Alessandra; Cappa, Stefano F.; Vecchi, Tomaso; Crespi, Chiara (Frontiers in Psychiatry, 2020)
Covid-19 pandemic is burning all over the world. National healthcare systems are facing the contagion with incredible strength, but concern regarding psychosocial and economic effects is critically growing. The PsyCovid Study assessed the influence of psychosocial variables on individual differences in the perceived impact of Covid-19 outbreak on health and economy in the Italian population. Italian volunteers from different regions completed an online anonymous survey. Main outcomes were the perceived impact of Covid-19 outbreak on health and economy. A two-way MANOVA evaluated differences in main outcomes, with geographical area (northern, central and southern regions) and professional status (healthcare workers or not) as factors. We then tested the relationship linking psychosocial variables (i.e. perceived distress and social isolation, empathy and coping style) to the main outcomes through two different mediation models. 1163 responders completed the survey (835 females; mean age: 42±13.5 y.o.; age range: 18-81 y.o.) between March 14 and 21, 2020. Healthcare workers and people living in northern Italy reported significantly worse outbreak impact on health, but not on economy. In the whole sample, distress and loneliness were key variables influencing perceived impact of Covid-19 outbreak on health, while empathy and coping style affected perceived impact on economy. Covid-19 pandemic is a worldwide emergency in term of psychological, social and economic consequences. Our data suggests that in the Italian population actual differences in individual perception of the Covid-19 outbreak severity for health are dramatically modulated by psychosocial frailty (i.e., distress and loneliness). At the same time, problem-oriented coping strategies and enhanced empathic abilities increase people awareness about the severity of the impact of Covid-19 emergency on economics. There is an immediate need of consensus guidelines and healthcare policies to support interventions aimed to manage psychosocial distress and increase population resilience towards the imminent crisis.